The Effect of Mudharabah Financing Risks and Musyarakah Financing Risks on the Return on Assets of Islamic Commercial Banks in Indonesia - Kasmawati Kasmawati; Mustafa Kamal; Rohima Rohima; Rani Munika (Khazanah Sosial, 2022)
This study aims to analyze the effect of mudharabah financing risk and musyarakah financing risk on the Return On Assets of Shari'a Commercial Banks in Indonesia from 2016 to 2020. Sharia Commercial Bank is a Sharia bank that is related to sharia principles in carrying out its activities. The population in this study was 14 Islamic commercial bank companies in the 2016-2020 period. The sampling technique used is purposive sampling with a total sample of 11 companies. The data used is secondary data in the form of annual financial statements obtained from the website (www.ojk.co.id). The analytical technique used in this study is multiple linear regression. The results showed that the risk of mudharabah financing has a significant influence on Return On Assets, meanwhile, the risk of musyarakah financing did not affect the Return On Assets of Shari'a Commercial Banks in Indonesia during the 2016-2020 period.